Welfare and the Family: The U.S. Experience - Murray, Charles (Journal of Labor Economics, 1993)
After describing the development and dimensions of the American welfare system, this paper explores the relationship of illegitimacy to welfare. Alternative measures of illegitimacy are discussed. The relationship of the welfare package and the illegitimacy ratio is examined over time and across states, by race. A bivariate relationship of welfare and illegitimacy exists among whites, but not among blacks. Among blacks, a strong cross-state relationship exists between density of the black population and the illegitimacy ratio. The relationship is robust, persisting after controlling for a variety of demographic and economic variables, and persisting across time.